Efficacy and safety of systemic treatments in psoriatic arthritis: a systematic review, meta‐analysis and GRADE evaluation. (2nd May 2019) - Dressler, C.; Eisert, L.; Pham, P.A.; Nast, A.
Abstract: Twenty per cent of patients with plaque psoriasis also have psoriatic arthritis – a disease affecting joints and entheses. Different treatment options exist but currently no succinct systematic overview exists. A systematic review of approved systemic treatments for psoriatic arthritis was conducted. We systematically searched in three databases (last update September 2017). Data were extracted for ACR20/50, HAQ‐DI, SF‐36 and adverse/serious adverse events after 16–24 weeks. We assessed the quality of evidence using GRADE. Twenty trials were included. Three trials compared two active substances. Results for ACR20 were infliximab + methotrexate vs. methotrexate: RR 1.40 (95% CI 1.07–1.84) very low quality evidence; ixekizumab Q2W vs. adalimumab Q2W: RR 1.08 (95% CI 0.86–1.36) very low quality, leflunomide vs. methotrexate: RR 1.01, (95% CI 0.84–1.21) low quality. Eighteen drug vs. placebo comparisons were included. For ACR20/50, HAQ‐DI and SF‐36, the active treatment was efficacious and the quality of the evidence was mostly moderate to low (15 of 18 comparisons). The quality of evidence for (serious) adverse events was mostly low; differences were rare. In three placebo‐controlled comparisons, leflunomide, MTX and sulfasalazine failed to show statistical superiority for ACR. Besides the established treatment of anti‐TNF antibodies and ustekinumab for psoriatic arthritis, the newer treatment options of IL17 antibodies and apremilast are also effective for the treatment of psoriatic arthritis. Based on just one comparative trial and one drug each, the new class of anti‐IL 17 antibodies appears to be equally effective as the group of anti‐TNF antibodies; for apremilast, this is yet unclear.